Innovation in product and process: the implications for technology strategy. (1st January 2000) - Jones, Oswald; Tang, Nelson
The ability of firms to introduce new products and to improve their manufacturing processes is central to the creation of competitive advantage. However, Utterback and Abernathy argue that during the course of a product life-cycle there is a gradual shift in emphasis from product to process innovations. It is therefore essential for managers to understand the interaction of product and process during the shift from introduction to maturity. Zahra et al. integrate the frameworks developed by Miles and Snow and Porter to give five generic strategic types: Defender, Cost Leader, Analyser, Cost Differentiator, Prospector. Of central importance to the model is whether managers concentrate their resources on product or process innovation. To examine the relationship between product and process innovation, research was carried out in two mid-corporate manufacturing companies. PAC and Stern are suppliers to the major motor manufacturers but are not direct competitors. The two companies are classified as different strategic types; PAC has adopted an "analyser" strategy and Stern is pursuing a "cost leadership" strategy. The results confirm that generic strategies have direct implications for technology strategy and for the emphasis on product or process innovation.